Socio-technical trust in blockchain-based halal certification: an integrative governance framework - Reza Nurul Ichsan; Budi Alamsyah Siregar; Dewi Suma; Ega Siddik (Jurnal Mantik, 2026)
The slow manual halal certification process in Indonesia and declining public trust in the Halal Product Assurance Agency pose crucial challenges. This study aims to systematically review the literature on digital transformation in halal certification bodies, focusing on the integration of blockchain technology, trust-building mechanisms, and governance challenges. Using the Systematic Literature Review (SLR) method guided by PRISMA, 32 peer-reviewed articles (2020–2025) were thematically analyzed. Key findings indicate that blockchain has the potential to improve transparency and efficiency. However, its success depends heavily on building socio-technical trust that combines technological reliability and institutional credibility as well as the ability to overcome governance barriers such as regulations and bureaucratic resistance. It concludes that effective digital transformation requires a holistic synergy between technological innovation, institutional reform, and public trust